Law Enforcement Analysis Against the Night Entertainment Business Owner During Covid-19 Pandemic - Parman. Bm. Nainggolan; Markoni Markoni; Wasis Susetio (Journal of Multidisciplinary Academic, 2021)
Indonesia was declared as a health emergency state, due to the Covid-19 pandemic in March 2020. Here, the Indonesian government and both central and regional, was taken a policy by issuing new regulations that limit community interaction and productivity with aimed to accelerating the response to covid-19, however the impact on the weakening of the community's economic development. Night entertainment business actors who were directly affected by the covid-19 virus, during the covid-19 pandemic had closed their businesses for about 4 months, and laid off their employees by cutting salaries / wages by 50% and some even did not provide salaries / wages until the employee is re-employed. Thus, to cover expenses or to keep earning income, there are nightlife business actors who secretly open their businesses such as karaoke in rooms, restaurants / cafes with virtual music while still providing alcoholic drinks in the Regional Regulations who allow a trading alcoholic drink. The trading situation it makes no legal certainty in the night entertainment business community to run their business because there are no definite new rules for carrying out their business. Thus, in the Covid-19 pandemic, which until now is still increasing who are exposed and on the other hand the nightlife business actors must continue their business while maintaining to avoid the spread of Covid-19, it is necessary to have binding and strict legal rules, so that laws or regulations against night entertainment business actors during the Covid-19 pandemic can be enforced.